Relationship between the Composition of Flavonoids and Flower Colors Variation in Tropical Water Lily (Nymphaea) Cultivars - Zhu, Manlan; Zheng, Xuchen; Shu, Qingyan; Li, Hui; Zhong, Peixing; Zhang, Huijin; Xu, Yanjun; Wang, Lijin; Wang, Liangsheng (PLOS ONE, 2012)
Water lily, the member of the Nymphaeaceae family, is the symbol of Buddhism and Brahmanism in India. Despite its limited researches on flower color variations and formation mechanism, water lily has background of blue flowers and displays an exceptionally wide diversity of flower colors from purple, red, blue to yellow, in nature. In this study, 34 flavonoids were identified among 35 tropical cultivars by high-performance liquid chromatography (HPLC) with photodiode array detection (DAD) and electrospray ionization mass spectrometry (ESI-MS). Among them, four anthocyanins: delphinidin 3-O-rhamnosyl-5-O-galactoside (Dp3Rh5Ga), delphinidin 3-O-(2″-O-galloyl-6″-O-oxalyl-rhamnoside) (Dp3galloyl-oxalylRh), delphinidin 3-O-(6″-O-acetyl-β-glucopyranoside) (Dp3acetylG) and cyanidin 3- O-(2″-O-galloyl-galactopyranoside)-5-O-rhamnoside (Cy3galloylGa5Rh), one chalcone: chalcononaringenin 2′-O-galactoside (Chal2′Ga) and twelve flavonols: myricetin 7-O-rhamnosyl-(1→2)-rhamnoside (My7RhRh), quercetin 7-O-galactosyl-(1→2)-rhamnoside (Qu7GaRh), quercetin 7-O-galactoside (Qu7Ga), kaempferol 7-O-galactosyl-(1→2)-rhamnoside (Km7GaRh), myricetin 3-O-galactoside (My3Ga), kaempferol 7-O-galloylgalactosyl-(1→2)-rhamnoside (Km7galloylGaRh), myricetin 3-O-galloylrhamnoside (My3galloylRh), kaempferol 3-O-galactoside (Km3Ga), isorhamnetin 7-O-galactoside (Is7Ga), isorhamnetin 7-O-xyloside (Is7Xy), kaempferol 3-O-(3″-acetylrhamnoside) (Km3-3″acetylRh) and quercetin 3-O-acetylgalactoside (Qu3acetylGa) were identified in the petals of tropic water lily for the first time. Meanwhile a multivariate analysis was used to explore the relationship between pigments and flower color. By comparing, the cultivars which were detected delphinidin 3-galactoside (Dp3Ga) presented amaranth, and detected delphinidin 3′-galactoside (Dp3′Ga) presented blue. However, the derivatives of delphinidin and cyanidin were more complicated in red group. No anthocyanins were detected within white and yellow group. At the same time a possible flavonoid biosynthesis pathway of tropical water lily was presumed putatively. These studies will help to elucidate the evolution mechanism on the formation of flower colors and provide theoretical basis for outcross breeding and developing health care products from this plant.